A Combined Effect of Mixed Multi-Microplastic Types on Growth and Yield of Tomato - Chijioke Emenike; Adeola Adelugba; Mason MacDonald; Samuel K. Asiedu; Raphael Ofoe; Lord Abbey (Microplastics)
Microplastics (MPs) are plastic particles ranging from 1000 to 5000 µm in diameter, posing a growing environmental and health risk. Composting is an excellent way to add nutrient-rich humus to the soil to boost plant development, but it also pollutes agricultural soil with MPs. Previous research has shown that MPs can threaten plant development, production, and quality, hence they must be studied. This study examined how a mixture of three MP types—polyethene (PE), polystyrene (PS), and polypropene (PP)—affected greenhouse tomato plant development. MP types were spiked at 1% w/w (MPs/soil) in tomato pots, whereas non-spiked growth medium was the control. Statistical analysis was conducted using an analysis of variance (ANOVA) and Tukey’s test (95% confidence) to compare treatments and controls. Soil spiked with MPs increased chlorophyll content (SPAD), transpiration rate, photosynthetic rate, and stomata conductance by 5.16%, 16.71%, 25.81%, and 20.75%, respectively, compared to the control but decreased sub-stomata CO2 concentration by 3.23%. However, MPs did not significantly affect tomato plant morpho-physiological features (p > 0.05). Biochemical analysis of tomato fruits showed significant (p < 0.05) reduction effects of MPs on carotenoid, total flavonoid, and sugar but increased protein, ascorbate, and peroxidase activity. However, there was no significant difference (p > 0.05) in the effects of the combined MPs on total phenolic content. These data imply that whereas MPs did not influence tomato plant physiological and morphological properties, tomato fruit biochemistry was reduced. This raise concerns that an increase in MPs in soils may reduce antioxidant content and negatively affect human health contributing to a decrease in food security.